1963
DOI: 10.1084/jem.118.6.919
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Stable Hemolysins of Group a Streptococci

Abstract: In the preceding paper (1) the materials and methods involved in the production of oxygen-stable hemolysins by Group A streptococci were described.It was shown that although a variety of unrelated materials such as RNA, serum albumin, serum a lipoprotein, tween 40, and triton X-205 could induce the production of hemolysin from resting streptococci, a number of similarities could be demonstrated among the resulting preparations of hemolysin. All were inhibited by lecithin, trypan blue, congo red, papain, chymot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

1964
1964
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 10 publications
0
12
1
Order By: Relevance
“…125, 126 Despite these challenges, analysis of crude preparations indicated that the active component of SLS was a peptide. 127–130 However, it was not until the year 2000 that transposon mutagenesis and DNA sequencing studies 131, 132 revealed that SLS was a RiPP. 133, 134 These genomic studies demonstrated that nine genes, sagABCDEFGHI , comprised the SLS operon (Figure 6).…”
Section: Linear Azole-containing Peptides (Laps)mentioning
confidence: 99%
“…125, 126 Despite these challenges, analysis of crude preparations indicated that the active component of SLS was a peptide. 127–130 However, it was not until the year 2000 that transposon mutagenesis and DNA sequencing studies 131, 132 revealed that SLS was a RiPP. 133, 134 These genomic studies demonstrated that nine genes, sagABCDEFGHI , comprised the SLS operon (Figure 6).…”
Section: Linear Azole-containing Peptides (Laps)mentioning
confidence: 99%
“…First, in experiments reported elsewhere in these studies it was found, after incubation of RNA hemolysin with tween and the subsequent resolution of the mixtures by DEAE cellulose chromatography, that the fraction containing the tween, which had 70 per cent of the hemolytic activity after the incubation, was not contaminated with RNA, within the limits of detection of the orcinol method (11). Second, in experiments reported recently by Egami and Koyama (12), RNA hemolysin labeled with C 14 amino acids was incubated with tween 40 and the mixture was resolved on DEAE cellulose.…”
Section: Discussionmentioning
confidence: 94%
“…These apparently para doxical effects are explicable by mutal transfer of SLS polypeptide among carrier substances [17,18]. Thus, after synthesis, the toxin polypeptide is tran sported into cell envelope and probably bound to an endogenous carrier site, transiently [19,20], U pon incubation with AF or azo dye having higher affin ity, SLS is transferred to exogenous carrier and se creted into m edium as the active exotoxin complex.…”
Section: Discussionmentioning
confidence: 99%